2021
DOI: 10.1039/d0sc06747d
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the stacking modes of nanosized metal–organic frameworks by morphology engineering for isomer separation

Abstract: Modulating different stacking modes of nanoscale metal-organic frameworks (MOFs) introduces different properties and functionalities but remains a great challenge. Here, we describe a morphology engineering method to modulate the stacking...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…With a similar strategy, they also synthesized several functionalized Zr-MONs, Hf-MONs, and Ce-MONs by using D 3h symmetric ligands bearing terpyridine group. [74][75][76] Replacing H 3 BTB with D 4h symmetric nickel-tetrakis(4-carboxyphenyl)porphyrin (Ni-TCPP), and using Zr 6 -cluster (Zr 6 (μ 3 -O) 4 (μ 3 -OH) 4 ) as [78]. Copyright 2021, The Royal Society of Chemistry.…”
Section: Modulator-assisted Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…With a similar strategy, they also synthesized several functionalized Zr-MONs, Hf-MONs, and Ce-MONs by using D 3h symmetric ligands bearing terpyridine group. [74][75][76] Replacing H 3 BTB with D 4h symmetric nickel-tetrakis(4-carboxyphenyl)porphyrin (Ni-TCPP), and using Zr 6 -cluster (Zr 6 (μ 3 -O) 4 (μ 3 -OH) 4 ) as [78]. Copyright 2021, The Royal Society of Chemistry.…”
Section: Modulator-assisted Methodsmentioning
confidence: 99%
“…As the amount of acetic acid increased, the morphology of NU-901 changed from nanosheets to interpenetrated nanosheets, and finally to nanoparticles. [78] Recently, they reported that the modulator not only regulated the growth of Zr-BTB nanosheets, but also played a key role in obtaining twisted or untwisted Zr-BTB nanosheets (Figure 6d). [79] Besides the often observed Zr 6 (μ 3 -O) 4 (μ 3 -OH) 4 cluster, Lin and co-workers reported that Zr-MOF nanosheets composed of unique Zr 12 -node (Zr 12 (μ 3 -O) 8 (μ 3 -OH) 8 (μ 2 -OH) 6 ) [80] and linear dicarboxylate linker can be prepared by employing formic acid and water as modulators (Figure 6e).…”
Section: Modulator-assisted Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is very important to note that structural tunability/adaptability is key feature of MOFs/PCPs. [17][18][19] Apart from such 3D architecture of MOFs, 2D MOFs/PCPs represent one class of materials which are potentially useful in energy storage, optoelectronic property, gas permeation, chemical sensing. [20][21][22][23][24] Structural designability/ tunability remained the most important advantage of such 2D MOFs/PCPs as well.…”
Section: Introductionmentioning
confidence: 99%
“…Combining organic linkers and inorganic metal node generate such MOFs/PCPs with potential voids. It is very important to note that structural tunability/adaptability is key feature of MOFs/PCPs [17–19] . Apart from such 3D architecture of MOFs, 2D MOFs/PCPs represent one class of materials which are potentially useful in energy storage, optoelectronic property, gas permeation, chemical sensing [20–24] .…”
Section: Introductionmentioning
confidence: 99%